Production and Promotion of Cocomesh and Cocofiber at PUT Manado State Polytechnic - Rudolf Estephanus Golioth Mait; Beldie Aryona Tombeg; Yollanda Lydia Lagarense; Don Radius Gerald Kabo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to increase the production and promotion of Cocomesh and Cocofiber products through innovation at the Center for Technology Excellence (PUT) of the Manado State Polytechnic. The focus of the study is on strategies for developing more efficient production and more effective promotion, considering the challenges faced by the local coconut fiber industry in terms of production process efficiency and product promotion appeal. This study uses the SWOT analysis method to identify strengths, weaknesses, opportunities, and threats, and involves data collection through interviews, field observations, and distributing questionnaires to consumers and business partners.The results of the study indicate that the application of innovative technology can increase the efficiency of Cocomesh and Cocofiber production, although existing promotional strategies still need strengthening, especially in the use of digital media. Collaboration with local industries and empowerment of coconut farmers have a positive impact on the scarcity of raw materials and the economic growth of the surrounding community. This study also contributes to the development of a national innovation system through collaboration between educational institutions and industry. It is hoped that through more innovative strategies and stronger promotions, Cocomesh and Cocofiber products can compete nationally and internationally, while providing significant social, economic, and environmental benefits